PERAN BADAN KERJASAMA ANTAR DESA DALAM PERLINDUNGAN, PENGELOLAAN, PELESTARIAN HASIL PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI KABUPATEN BANYUASIN - Helda Fitriani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2023)
This research audit was conducted to find out the overall protection, management, and conservation efforts that were carried out to provide legal guarantees, maintain sustainability, and expand the results of the participatory developments that were established by PNPM and facilitated by the guarantees). The problem faced by BKAD is that it is a sustainable arrears from the SPP group in iBanyuasin. This research takes up the issue by investigating the role of BKAD in protecting, managing, and preserving the results of the implementation of PNPM in Banyuasin. The qualitative qualitative method was chosen to examine the problem that is being investigated. The research data were collected by means of in-depth interviews, observations, and documentation. The determination of informants was carried out by purposive sampling and snowball sampling. Data is validated through consistent participation, observation, member checking, and triangulation. The data were analyzed qualitatively, which consisted of data collection, data reduction, data presentation, and data verification. The research findings cover three problems. First, BKAD takes safeguards aimed at inventorying SPP assets and properties through discussions. Second, BKAD carries out a management program by restructuring client loans, collaborating with all the teams involved in PNPM. Third, the conservation efforts carried out by BKAD have resulted in sustainable SPP.